2020
DOI: 10.1038/s41418-020-0495-2
|View full text |Cite
|
Sign up to set email alerts
|

TRIM proteins in autophagy: selective sensors in cell damage and innate immune responses

Abstract: Autophagy, a main intracellular catabolic process, is induced in response to a variety of cellular stresses to promptly degrade harmful agents and to coordinate the activity of prosurvival and prodeath processes in order to determine the fate of the injured cells. While the main components of the autophagy machinery are well characterized, the molecular mechanisms that confer selectivity to this process both in terms of stress detection and cargo engulfment have only been partly elucidated. Here, we discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 121 publications
(221 reference statements)
0
111
0
1
Order By: Relevance
“…VAMP8 and SNAP29). TRIM family proteins, including TRIM5, are increasingly recognized for modulating the actions and activities of these core autophagy factors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…VAMP8 and SNAP29). TRIM family proteins, including TRIM5, are increasingly recognized for modulating the actions and activities of these core autophagy factors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, TRIM5 is one member of the large TRIM protein family. A very high percentage of the ~70 TRIMs in human genome act in regulating inflammatory signaling and antiviral defense and are increasingly linked to autophagy (29). Our findings presented here could potentially provide a groundwork for understanding the molecular underpinnings of these other TRIMs and how they coordinate their activities in autophagy and inflammation.…”
Section: Discussionmentioning
confidence: 77%
“…VAMP8 and SNAP29). TRIM family proteins, including TRIM5, are increasingly recognized for modulating the actions and activities of these core autophagy factors (29).…”
Section: Introductionmentioning
confidence: 99%
“…Tripartite motifcontaining protein 16 (trim16) gene is a part of tripartite motif family which has also been associated with QTL regions for A. hydrophila resistance in the hybrid cat sh [21]. Several studies have showed the involvement of this family of genes with signaling pathways for activation of murine macrophages [21], autophagic response [42], and interleukin secretion [43]. Interleukin 12 Receptor Subunit Beta2 (Il12rb2) is responsible in regulation of receptors to interleukin-12, a proin ammatory cytokine produced by phagocytic cells already identi ed in response to A. hydrophila infection [44].…”
Section: Genome Wide Association Analysis (Gwas)mentioning
confidence: 99%